UNIVERSITY LECTURERS’ VIEWS ON DISTANCE EDUCATION DURING THE COVID-19 PANDEMIC: UKRAINIAN-LATVIAN COMPARATIVE STUDIES - Malykhin, Oleksandr; Usca, Svetlana; Aristova, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The main purpose of the study was to compare and contrast Ukrainian and Latvian university lecturers’ views on distance education (teaching and learning) caused by the sudden interruption of the face-to face instruction due to the COVID-19 pandemic. The study was also targeted at investigating university lecturers’ readiness to respond to the educational challenges during the pandemic. The international team of researchers set up a web-based questionnaire aimed at self-assessing Ukrainian and Latvian university lecturers’ digital literacy knowledge and skills and finding out their attitudes towards current educational changes. Having absolutely identical content the web-based questionnaire was presented in the Ukrainian, Latvian and English languages. The research sample which was selected with the use of a voluntary response sampling technique consisted of 60 university lecturers from Kyiv National University of Technologies and Design (Kyiv, Ukraine), Taras Shevchenko National University of Kyiv (Kyiv, Ukraine), National Aviation University (Kyiv, Ukraine), Rezekne Academy of Technologies (Rezekne, Latvia). Qualitative data analysis covered a conscientious summing-up of the information received, displaying the processed data in the form of tables and pie charts, comparing and generalizing the data received in Ukraine and Latvia, discussing the obtained findings and making logical conclusions how to cope with educational challenges.